Cultural Approach Based on Bhinneka Tunggal Ika in Horizontal Conflict Resolution - Firli Bahuri; Agus Surono; Adnan Hamid; Irwansyah Irwansyah (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to analyse the characteristics of horizontal conflict in Indonesia and evaluate the significance of a cultural approach based on Bhinneka Tunggal Ika (Unity in Diversity) for conflict resolution. This study also examines the contribution of a cultural approach to more effective, sustainable conflict resolution strategies, aligned with the Asta Gatra framework as a pillar of national resilience. Study Design/Methodology/Approach: This study uses an interpretivist-phenomenological philosophy with an empirical-inductive method and an archival study strategy to identify patterns of culture-based conflict resolution in various regions of Indonesia. The data were obtained through a literature review, document analysis, and stakeholder interviews and then analysed reductively to ensure links with the socio-cultural, ideological, and security dimensions of Asta Gatra. Findings: The research results indicate that a cultural approach based on Bhinneka Tunggal Ika (Unity in Diversity) has significant potential to reduce horizontal conflict and strengthen social cohesion. However, implementation limitations due to a lack of integration with policy, development, and the legal system require collaboration between the government, indigenous communities, and legal institutions as a key to national stability.